Various Prebiotics and Probiotics, Their Usage and Importance in Maintaining Normal Microflora in Animal - Ahmad, Muhammad Talha; khan, Danyal; khan, Sidra; Ahmed, Sohail; Amin, Muhammad Waqas; Gulshan, Muhammad Zahid; Adrian Shah, Shahzada Khurram; Shafaqat, Ambreen; Zia, Munazza; Noor, Maaz (Indus Journal of Bioscience Research, 2025)
Maintaining balanced microflora in animals is essential for health, immunity, and productivity, particularly considering the increasing global demand for antibiotic-free animal products. This review examines the contributions of prebiotics and probiotics, separately and in combination as synbiotics, to gastrointestinal health and the enhancement of animal performance. This review consolidates contemporary data regarding these therapies’ mechanisms, uses, and advantages, highlighting their capacity to foster microbial stability, improve nutrient absorption, and augment immunological responses across diverse animal species, including poultry, swine, ruminants, and aquaculture. Key themes, including the effectiveness of prebiotic and probiotic strains, and discrepancies in the literature concerning doses, combinations, and species-specific treatments are examined. The review additionally analyzes the synergistic effects of synbiotics, which enhance the advantages of these chemicals. This review examines the current research landscape, identifies significant knowledge gaps, and provides insights into the difficulties and potential for enhancing microbial-based techniques in animal production systems. The results underscore the promise of prebiotics and probiotics as sustainable substitutes for antibiotics, enhancing animal welfare and production while mitigating the environmental effects of livestock systems. The review culminates with essential recommendations for future research, highlighting the necessity for longitudinal investigations, established methodology, and the investigation of innovative microbiological possibilities. It enhances the comprehension and implementation of microbial-based therapies, providing a basis for superior health management and sustainable practices in animal agriculture.